PENGARUH LAYANAN KELENGKAPAN BUKU DI PERPUSTAKAAN KAMPUS B UNIVERSITAS AIRLANGGA TERHADAP KEPUASAN MAHASISWA - Aulia Novia Safitri; Aneke Laksmi Mahdani; Ika Rohmah (Triwikrama: Jurnal Ilmu Sosial, 2024)
This study aims to analyze the effect of book completion services at the Campus B Library of Airlangga University on student satisfaction. The study used a quantitative approach with a survey method of 100 randomly selected respondents. The results showed that book completion services had a significant effect on student satisfaction, with a correlation value of 0.687 (p <0.01). Supporting service factors also contributed significantly (correlation value 0.669, p <0.01). The results of the regression analysis showed that 53.1% of the variation in student satisfaction could be explained by book completion services and supporting service factors. These findings indicate the importance of relevant book collections and supporting facilities in improving student experience. The implication of this study is the need for libraries to continue to update book collections and improve service quality in order to optimally meet students' academic needs.